WF16 - Mithen, Steven (Council for British Research in the Levant, 2023)
WF16 is located in the spectacular Wadi Faynan area of southern Jordan. Evaluation of the site was undertaken between 1997 and 2006 with a monograph, detailing results of the evaluation, published in 2007 (Finlayson & Mithen 2007). Material remains at the site indicate that settlement occurred during the Pre-Pottery Neolithic A (PPNA) period, with a suite of radiocarbon dates indicating occupation between 11,600 and 10,200 BP (Before Present–before 1950). Originally defined by Kathleen Kenyon during excavation at Jericho in the 1950s, the PPNA is traditionally seen as the earliest manifestation of an agricultural economy in the world, with villages occupied by sedentary groups practicing some form of cultivation. The PPNA brought to an end more than two million years of hunting and gathering and laid the foundations for the first civilisations. Despite more than 50 years of research, our understanding of PPNA society has remained limited. The excavation of WF16 offers the potential to significantly enhance our understanding of the PPNA and the origins of the Neolithic.